Landscape genetics, adaptive diversity and population structure in Phaseolus vulgaris. Issue 4 (3rd November 2015) - Rodriguez, Monica; Rau, Domenico; Bitocchi, Elena; Bellucci, Elisa; Biagetti, Eleonora; Carboni, Andrea; Gepts, Paul; Nanni, Laura; Papa, Roberto; Attene, Giovanna
Summary: Here we studied the organization of genetic variation of the common bean ( Phaseolus vulgaris ) in its centres of domestication. We used 131 single nucleotide polymorphisms to investigate 417 wild common bean accessions and a representative sample of 160 domesticated genotypes, including Mesoamerican and Andean genotypes, for a total of 577 accessions. By analysing the genetic spatial patterns of the wild common bean, we documented the existence of several genetic groups and the occurrence of variable degrees of diversity in Mesoamerica and the Andes. Moreover, using a landscape genetics approach, we demonstrated that both demographic processes and selection for adaptation were responsible for the observed genetic structure. We showed that the study of correlations between markers and ecological variables at a continental scale can help in identifying local adaptation genes. We also located putative areas of common bean domestication in Mesoamerica, in the Oaxaca Valley, and the Andes, in southern Bolivia‐northern Argentina. These observations are of paramount importance for the conservation and exploitation of the genetic diversity preserved within this species and other plant genetic resources.